Drug Use and Multiple Sex Partners Among Homeless Ex-Offenders: Secondary Findings From an Experimental Study. Issue 3 (May 2016) - Nyamathi, Adeline M.; Zhang, Sheldon X.; Wall, Sarah; Hall, Elizabeth A.; Salem, Benissa E.; Farabee, David; Faucette, Mark; Yadav, Kartik
Abstract : Background: Transitioning into society after release from incarceration presents real challenges for male offenders; in California, up to 60% return to prison within 3 years after release. The risk for ongoing drug use and having sex with multiple partners is a significant challenge for ex-offenders preparing to enter the community. Objectives: The aims are to describe drug use and sexual behavior (sex with multiple partners) prior to incarceration and 6 and 12 months after study enrollment using data obtained as part of a randomized controlled trial. Methods: This is a planned secondary analysis of data obtained as part of a randomized controlled trial designed to study the effects of intensive peer coaching and nurse case management, intensive peer coaching, and brief nurse counseling on hepatitis A and B vaccination adherence compared to a usual care control treatment that also included brief peer coaching and brief nurse counseling. Self-report data from subjects enrolled at one residential drug treatment facility in Los Angeles were captured at three time points: baseline and 6- and 12-month follow-up. Results: Findings showed substantive and significant reductions in drug use and engaging in sex with multiple partners 6 months after enrollment into the study compared to the baseline data, but results did not differ by study condition. At 12-month follow-up, drug use and sex with multiple partners increased but remained less than at baseline levels. Discussion: Sustaining reductions in drug use and engaging in sex with multiple partners remains a challenge after incarceration.